IMPLEMENTATION OF WORK ENVIRONMENT IN SUPPORTING EMPLOYEE PERFORMANCE IN SOUTHEAST PROVINCE MENTAL HOSPITAL - La Ode Muhammad Elwan; Sartono; Siti Khadijah (Halu Oleo University, 2023)
The purpose of this study was to determine the application of the work environment and employee performance at the Mental Hospital of Southeast Sulawesi Province. The method used is descriptive qualitative. Data were analyzed using an interactive model according to Miles, Huberman & Saldaña (2014) in (Elwan et al., 2022). The results of the study show that the implementation of the work environment for employees of the Mental Hospital in Southeast Sulawesi Province, both physical and non-physical work environment, has made a positive contribution to achieving success in carrying out a job for all employees. Likewise with the condition of the non-physical work environment supports a harmonious working relationship through good communication between employees in the Mental Hospital of the Province of Southeast Sulawesi. Employee performance at the Mental Hospital of the Province of Southeast Sulawesi can already be stated as good according to employee performance indicators, namely timeliness of work, compliance with work rules and systems, satisfactory quantity and quality of work, completion of work, and good morale, effective relations and communication, able to contribute and added value as well as responsibility for organizational assets.